(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article describes main current trends and features of the Eurodollar market, the basic terms and principles providing the formation of a single market and the financial sector in the European Union, in addition, on the basis of result of research in this market given practical recommendations and scientific proposals for the sustainable development of the national financial market.